Possessed by the Right Hand: The Problem of Slavery in Islamic Law and Muslim Cultures by Bernard K. Freamon (American Journal of Islam and Society, 2020)
The last several years have seen an explosion of scholarly interest in slavery in the Islamic world and other global contexts. Recent contributions to this field include Jonathan A.C. Brown’s Slavery in Islam and Mary Ann Fay’s edited volume, Slavery in the Islamic World; a new edition of Orlando Patterson’s seminal Slavery and Social Death has also recently been published with a new preface.With his ambitious and erudite monograph, Possessed by the Right Hand: The Problem of Slavery in Islamic Law and Muslim Cultures, Bernard K. Freamon intervenes in this field from the perspective of a legal scholar. His legal focus emerges most strongly in the final two chapters, in which he urges Muslims and scholars of Islam to confront the continued legacy of slavery in the contemporary Islamic world. This exhortation is embedded within a broadly transhistorical and transregional study of slavery in the Middle East and Indian Ocean, ranging from ancient Persia to 19th-century Zanzibar to contemporary Arabia. Most of this historical material is based on a synthesis of secondary scholarship, rather than a new analysis of primary sources.Download